Digital Political Dynamics: The Influence of Social Media on Election Participation, in the 2024 Election - Sulistya A, Astrid; Lianingsih, Nestia (Communication in Research and Publications (CRP), 2024)
The 2024 election in Indonesia is an important moment that shows the significant role of social media in increasing voter participation, especially among the younger generation. This study uses a mixed methods approach to analyze the influence of social media on political participation. The results of a survey of 1,000 respondents showed that 85% actively use social media, and 75% feel more involved in the election process after being exposed to digital campaigns. Platforms such as Facebook, Instagram, Twitter, and TikTok are the main channels for disseminating political information. Content analysis shows that socio-economic issues, pluralism, and the environment are the dominant themes that attract the attention of young voters. This study highlights the importance of strict regulations to prevent the spread of false information and ensure the quality of democracy through social media.